2014
DOI: 10.3122/jabfm.2014.01.130167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginger for Nausea and Vomiting in Early Pregnancy: A Meta-Analysis

Abstract: Background: Nausea and vomiting in early pregnancy (NVEP) is commonly encountered in family medicine. Ginger (Zingiber officinale) is a popular nonpharmacological treatment but consensus of its use is lacking.Methods: We conducted a meta-analysis of clinical trials using ginger for NVEP as published in PubMed and EMBASE, CINAHL, Cochrane Library, and all EBM reviews. Studies satisfying 3 criteria were selected: (1) randomized placebo-controlled design; (2) use of ginger or Z. officinale; and (3) extractable da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 38 publications
4
52
0
6
Order By: Relevance
“…One meta-analysis of two studies [19,29] in this SR showed that ginger significantly decreased nausea symptoms when compared to placebo. When taking into account that other SRs [10,16,17,35,36] as well as the above-mentioned 7 concluded that ginger had beneficial effects on nausea during pregnancy (together with the findings of this SR), it is probably safe to assume that ginger has potential as a possible anti-emetic drug-alternative during pregnancy. The theoretical physiological mechanism by which ginger affects the digestive system also supports this theory.…”
Section: Discussionmentioning
confidence: 83%
“…One meta-analysis of two studies [19,29] in this SR showed that ginger significantly decreased nausea symptoms when compared to placebo. When taking into account that other SRs [10,16,17,35,36] as well as the above-mentioned 7 concluded that ginger had beneficial effects on nausea during pregnancy (together with the findings of this SR), it is probably safe to assume that ginger has potential as a possible anti-emetic drug-alternative during pregnancy. The theoretical physiological mechanism by which ginger affects the digestive system also supports this theory.…”
Section: Discussionmentioning
confidence: 83%
“…Research suggests that ginger is an effective antiemetic treatment for these conditions (Chaiyakunapruk et al 2006;Ryan et al 2012;Thomson et al 2014). However, most investigations use encapsulated sources of ginger, hence bypassing oral sensory stimulation.…”
Section: Nausea and Vomitingmentioning
confidence: 98%
“…Recently, Thomson & coworkers [11] performed a meta-analysis of six studies with the aim to assess the clinical efficacy of ginger in nausea and vomiting in early pregnancy (NVEP) [11]. The use of ginger (1 g daily) for at least 4 days was found to be associated with a 5 fold likelihood of improvement in NVEP, thus suggesting that ginger is an effective non-pharmacological treatment for NVEP [11].…”
Section: Discussionmentioning
confidence: 99%